Prevalence and associated factors of delayed sputum smear conversion in patients treated for smear positive pulmonary tuberculosis: a retrospective follow up study in Sabah, Malaysia - Khor, Linghui Amanda; A. Wahid, Ulfa Nur Izzati; Ling, Lee Lee; Liansim, Sarah Michael S.; Oon, Jush’n; Balakrishnan, Mahendran Naidu; Ng, Wei Leik; Cheong, Ai Theng (Public Library of Science, 2023)
Introduction: Tuberculosis remains a major health problem globally and in Malaysia, particularly in the state of Sabah. Delayed sputum conversion is associated with treatment failure, drug-resistant tuberculosis and mortality. We aimed to determine the prevalence of delayed sputum conversion among smear positive pulmonary tuberculosis (PTB) patients and its associated factors in Sabah, Malaysia. Methods: A retrospective follow up study on all patients newly diagnosed with smear positive pulmonary tuberculosis from 2017 to 2019 was conducted at three government health clinics in Sabah, utilizing data from a national electronic tuberculosis database and medical records. Descriptive statistics and binary logistic regression were applied for data analysis. The outcome of the study was the sputum conversion status at the end of the two-month intensive treatment phase with either successful conversion to smear negative or non-conversion. Results: 374 patients were included in the analysis. Our patients were generally younger than 60 years old with no medical illness and varying proportions of tuberculosis severity as judged by radiographic appearance and sputum bacillary load upon diagnosis. Foreigners constituted 27.8% of our sample. 8.8% (confidence interval: 6.2–12.2) did not convert to smear negative at the end of the intensive phase. Binary logistic regression showed that older patients 60 years old (adjusted odds ratio, AOR = 4.303), foreigners (AOR = 3.184) and patients with higher sputum bacillary load at diagnosis [2+ (AOR = 5.061) and 3+ (AOR = 4.992)] were more likely to have delayed sputum smear conversion. Conclusion: The prevalence of delayed sputum conversion in our study was considerably low at 8.8% with age 60 years old, foreigners and higher pre-treatment sputum bacillary load associated with delayed conversion. Healthcare providers should take note of these factors and ensure the patients receive proper follow up treatment.